8 - La coopération Arabo-Sénégalaise - Charbel ZAROUR (Africa Development, 1986)
Senegal comes second - if not first - among countries having received Arab aid in the 1976-1984 period. Regarding Afro-Arab co-operation, the case of Senegal is in teresting in many respects: two of the major African projects partly funded by Arab sources were carried out in this country. These are the OMVS project (the Diama and Manantalli dams) and that of the Chemical Industries in Senegal (ICS); contrary to the other African countries, in Senegal, Arab aid to projects was not oriented as it is usually done to road or in frastructure projects but rather toward sectors - agriculture, water - which determine the future of this country in the long run; as proposed to the Western countries policy, that of Arab countries tried to lay more emphasis on food self-sufficiency and on the tapping of available water resources; furthermore their interest in projects which call for intra-regional cooperation strangely opposes the dominant Northern countries' strategy; finally, with the high volume of non-project Arab aid granted to Senegal between 1980 and 1984, the country was in a position to cope with its external problems. But in view of the fact that this type of aid was given implicitly in conjunction with Western donors, one feels that non-project Arab aid, under such a conditon, fits in with North-South relationships. Although the Arab-Senegalese co-operation brought about sig nificant results, in the future it will have to face problems arising from the Arab debt burden and from the improvement of trade relationships.